2010
DOI: 10.1002/ppul.21125
|View full text |Cite
|
Sign up to set email alerts
|

Does the 6‐min walk test correlate with the exercise stress test in children?

Abstract: Is there a correlation between the 6-min walk and aerobic fitness in children? We studied healthy and cystic fibrosis (CF) subjects age 8-20 years using the 6-min walk test, treadmill graded exercise stress test, and spirometry. Six-minute walk distance (6MWD) and the product of 6MWD and body weight (6MWORK) were related to aerobic capacity. Data were analyzed using Student's t-test and Pearson correlation. 13 healthy subjects [9 females, mean age 15.8 +/- 3.6 years, % predicted forced expiratory volume in one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 18 publications
2
31
1
1
Order By: Relevance
“…This value falls within previously reported rates, (7,8,15,18) which range from 25% to 66%. (26) Functional performance on the six-minute walk test in patients with cystic fibrosis…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This value falls within previously reported rates, (7,8,15,18) which range from 25% to 66%. (26) Functional performance on the six-minute walk test in patients with cystic fibrosis…”
Section: Discussionsupporting
confidence: 77%
“…However, the authors did not analyze the distances covered. Lesser et al (15) administered the 6MWT to healthy individuals and cystic fibrosis patients (mean age: 14.3 ± 3.8 years). The 6MWD was shorter among the cystic fibrosis patients than among the controls (468 ± 68 m vs. 557 ± 73 m, respectively; p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The six-minute walking test (6MWT) has emerged as a common approach, and recent normative data have extended its application. 13 --15 The 6MWT has shown good validity and reliability, and is considered as the more relevant test that reflects physical activities of daily living, as well as cardiopulmonary fitness in healthy children 16,17 and in children with various diseases. 14,15,18 --20 Therefore, in addition to the assessment of cardiopulmonary and functional status, it has been reported that 6MWT could be a reliable parameter to predict peak oxygen uptake (VO 2 peak) in patients with varied diseases; 21,22 however, additional data linking the 6MWT performance to selected physiological measures of gas exchange were needed to optimize the use of this test.…”
Section: Introductionmentioning
confidence: 99%
“…Normal values for 6MWD for children have recently been published. [66][67][68][69] However baseline 6MWD is not a predictor of survival, neither when expressed as an absolute distance in meters nor when adjusted to reference values expressed as z score or as percentage of predicted value. 12,70 Cardiopulmonary exercise testing in children over 7 years of age is useful to determine peak oxygen consumption, ventilator efficiency slope (VE/VCO2), and anaerobic threshold.…”
Section: Discussionmentioning
confidence: 99%